2016
DOI: 10.3892/ol.2016.4903
|View full text |Cite
|
Sign up to set email alerts
|

HPV strain distribution in patients with genital warts in a female population sample

Abstract: The incidence of human papillomavirus (HPV) in the human cancer domain is still a subject of intensive study. In this study, we examined cervical swab samples from 713 females with genital warts, and tested the samples for high- and low-risk genital HPV. HPV genotyping was assessed using a Genotyping test that detects HPV by the amplification of target DNA using polymerase chain reaction and nucleic acid hybridization. In total, we detected 37 anogenital HPV DNA genotypes [6, 11, 16, 18, 26, 31, 33, 35, 39, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
2
33
0
1
Order By: Relevance
“…All three had a history of penile condyloma, and in one case oncogenic HPV had been detected in the tumor (43). Similar results were shown by other studies, with no difference in incidence between uncircumcised and circumcised men and with no protection against HPV infection (44)(45)(46). However, some studies have shown a protective effect in comparison with a control group.…”
Section: Prevention Of Hpv Infection In Mensupporting
confidence: 84%
“…All three had a history of penile condyloma, and in one case oncogenic HPV had been detected in the tumor (43). Similar results were shown by other studies, with no difference in incidence between uncircumcised and circumcised men and with no protection against HPV infection (44)(45)(46). However, some studies have shown a protective effect in comparison with a control group.…”
Section: Prevention Of Hpv Infection In Mensupporting
confidence: 84%
“…HPV cotesting can increase the interval period for cervical screening to 5 years under the current guidelines. Similar studies on HPV genotyping of anogenital warts have shown that a significant proportion of these lesions harbor high-risk HPV in combination with low-risk HPV [8]. While it is true that the majority of these infections would heal themselves within 2 years and cause no sequalae, a small number would persist and potentially cause cancers of the cervix, oropharynx, and oral cavity.Extragenital HPV is very common in patients with anogenital warts and has been documented in oral rinse samples as well [9].…”
mentioning
confidence: 89%
“…Squamous cell carcinoma may arise under the influence of various biological, physical, or chemical risk factors, such as human papillomavirus infection, ultraviolet radiation exposure, and diverse chemical carcinogens [186][187][188][189][190]. On an ultraviolet B (UVB) irradiation-induced skin carcinogenesis in vivo mouse model, the presence of CB1 and CB2 receptors in wild mice, compared to CB1/2 −/− knockdown mice, has correlated with increased tumorigenesis when benzanthracene was added alongside UVB; furthermore, the CB1/2 +/+ mice had a more prominent inflammation status, with increased TNFα and NF-κB compared to knockdown models, suggesting that CB1 and CB2 receptors are necessary in the pro-inflammatory tumoral response to UVB [191].…”
Section: Non-melanoma Cancersmentioning
confidence: 99%